Cyberl@b : a platform for learning english in costa rican public high schools = Cyberl@b : una plataforma para el aprendizaje del inglés en los colegios publicos de Costa Rica - Quesada Pacheco, Allen 1965- (2006)
This paper covers the design and development of a noncommercial software for learning and practicing English called CyberL@b. It was developed at the School of Modern Languages at the University of Costa Rica. Its target population focuses on 7th, 8th and 9th graders at six public high schools in diverse urban and rural settings in Costa Rica. CyberL@b uses interactive media resources designed to engage student in learning English within authentic contexts. Cyberlab was designed to create an environment that is unique in fostering the integration of the four language skills (listening, speaking, reading, and writing) through social interactions that are critical in EFL (English as a Foreign Language). An initial needs analysis of the six schools indicated that students considered the following to be important contributors to language learning: conversations with tourists, computer programs and video games, movies, and email of class notes. The implementation of CyberL@b indicates that when students engage in authentic activities relevant to their needs, they become more autonomous and self-directed in their learning. Teachers also adopt more learner-centered methods in their language teaching. On the basis of ongoing development and evaluation, a variety of approaches and technical strategies have been considered to allow students to engage in real-time authentic language learning activities through CyberL@b.
En Revista Actualidades Investigativas en Educación, vol. 6, no. 3 (setiembre - diciembre 2006)
Descripción basada en el contenido visto el 19 de setiembre, 2024